A genre analysis of Social Stories for individuals with autism spectrum disorders. (28th January 2023) - Yip, Jesse W C
Abstract : Developed by Carol Gray, Social StoriesTM is used to conduct behavioural interventions for individuals with Autism Spectrum Disorders (ASD) for the sake of developing and improving their social cognition, understanding, and skills. Existing guidelines for social story writing have been widely used by healthcare professionals. However, learners of social story writing face difficulties in following and comprehending the guidelines. This study aims to enhance understanding of social story composition from a discourse-pragmatic perspective. Drawing upon the framework of genre theory and move analysis, the study reveals and elucidates move structure, communicative purposes and rhetorical devices in Social StoriesTM. The study argues that Social StoriesTM are not narrative but a combination of informative and instructional discourse. This research suggests that genre study of Social StoriesTM supplements and facilitates learning and understanding of social story writing in healthcare professional training.